Does Trade With Labour Sending Countries Reduce Demand For Migrant Workers: A Lesson From Malaysia - Fariastuti, Djafar; Mohd Khairul, Hisyam Hassan (Asian Economic and Social Society, 2013)
This paper has three objectives. The first objective is to examine the long-run relationships among exports, imports, income and demand for migrant workers. This is followed by a causality test between these variables as the second objective. Finally, the third objective is to examine the extent to which exports, imports and income affect the demand for migrant workers. The study utilizes time series data and a Vector Auto Regressive (VAR) framework while examining two models, namely, Malaysia and Malaysia-Indonesia (Malindo). The findings show that all variables in the models are cointegrated. Generally, there is no short-run causality between variables in the models. In the long-run, causality runs from exports, imports and income to demand for migrant workers for the Malaysia model. There is bi-directional causality in the long-run between exports and imports, respectively, and demand for migrant workers in the Malindo model. Exports and demand for migrant workers in the Malaysia model, and exports and imports, respectively, and demand for migrant workers from Indonesia in the Malindo model are substitutes. Moreover, the income per capita for Malaysia has a non-significant negative effect on the demand for total migrant workers and a significant positive effect on the demand for migrant workers from Indonesia. The study suggests that trade can be a necessary instrument, but not a sufficient instrument for reducing the demand for migrant workers.